2011
DOI: 10.1007/s00425-011-1529-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the photosynthetic response induced by variation potential in geranium

Abstract: Electrical signals (action and variation potentials) caused by environmental stimuli induce a number of physiological responses in plants including changes in photosynthesis; however, mechanisms of these changes remain unclear. We investigated the influence of the variation potential on photosynthesis in geranium (Pelargonium zonale) under different conditions (control, low external CO₂ concentration, and actinic light absence). The variation potential caused by lamina burning induced a reduction in photosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
74
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 48 publications
(110 reference statements)
9
74
0
3
Order By: Relevance
“…It is known 22 that strong inactivation of the Calvin cycle can be one of mechanisms causing PSII damage when plants are under stress. As a result, it was possible that VP-induced photosynthesis dark stage inactivation 8,[11][12][13] stimulated PSII damage under heating.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known 22 that strong inactivation of the Calvin cycle can be one of mechanisms causing PSII damage when plants are under stress. As a result, it was possible that VP-induced photosynthesis dark stage inactivation 8,[11][12][13] stimulated PSII damage under heating.…”
Section: Resultsmentioning
confidence: 99%
“…9 Our previous analysis showed that increased heat tolerance of PSI was caused by an electrical signal-induced photosynthetic response 8 that was mainly related to photosynthesis dark stage inactivation. 8,[10][11][12][13] VP-induced response is caused by changes in intra-and extracellular pH that is concomitant with VP generation. [14][15][16] pH-dependent decrease of HCO 3 :CO 2 ratio, 16 changes in aquaporin permeability, 12 and (or) changes in carbonic anhydrase activity 14 are potential mechanisms by which VP influences dark stage photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ESs induce gene expression, [16][17][18] phytohormone synthesis, 17,19,20 phloem transport decrease, 21 changes in root absorption, 11 activation of respiration, [22][23][24][25][26] and inactivation of photosynthesis. 23,24,[26][27][28][29][30][31] Retivin et al 32 hypothesized that the ultimate role of these physiological changes is the increase of plant resistance to stressors. Indeed, it has been shown that ESs can have a positive influence on resistance to stressors at the whole plant level, 32 including increasing photosynthetic machinery resistance, 30,33 which is strongly connected with inactivation of photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…These 'AP-like' spikes can take the lead over the long-term depolarization in mimosa, sunflower and bean, 42,51,52 join the depolarization and form the first fast depolarization in pumpkin, geranium and pea, 24,30,46 and be generated during the depolarization in mimosa, sunflower, tomato, pumpkin and cucumber. 11,43,47,51,53 However, VP can occur without 'AP-like' spikes, as well.…”
Section: Introductionmentioning
confidence: 99%
“…As discriminated from slowly developing photosyn thetic responses that can be associated not only with elec tric but also with hormonal signals [19,23], an associa tion between the rapid inactivation of photosynthesis with AP and VP was confirmed in some works [27,29,31,32]. Nevertheless, the mechanism of the influence of the elec tric reaction on photosynthesis is still under discussion.…”
mentioning
confidence: 99%